Two‐Step Thermal Annealing: An Effective Route for 15 % Efficient Quasi‐2D Perovskite Solar Cells. Issue 8 (14th June 2021) - Romano, Valentino; Najafi, Leyla; Sutanto, Albertus Adrian; Schileo, Giorgio; Queloz, Valentin; Bellani, Sebastiano; Prato, Mirko; Marras, Sergio; Nazeeruddin, Mohammad Khaja; D'Angelo, Giovanna; Bonaccorso, Francesco; Grancini, Giulia
Abstract: Invited for this month's cover are collaborators from University of Pavia, École Polytechnique Fédérale de Lausanne, University of Messina and Istituto Italiano di Tecnologia. The cover picture shows the crystal structure of a Ruddlesden‐Popper quasi‐2D perovskite with chemical formula (PEA)2 MA39 Pb40 I121 (with PEA: phenylethylammonium and MA: methylammonium). The subscript 40 indicates the number of PbI6 octahedra separated by a double layer of PEA cations. Such quasi‐2D perovskites exhibit efficient photovoltaic performances and higher stability with respect to the pure 3D counterpart (MAPbI3 ). This article is part of the Special Collection on "Perovskite Materials and Devices". Read the full text of the article at 10.1002/cplu.202000777 . Abstract : "Two steps better than one : The use of quasi‐2D perovskites is a promising route towards stable and efficient photovoltaics." Read more about the story behind the cover in the Cover Profile and about the research itself (DOI: 10.1002/cplu.202000777 ).